Effect of Health Education on Improving the Knowledge among Diabetes Mellitus Patients in the Prevention of Diabetic Ulcer in Regional Hospital of Tidore Island - Haeril Amir; Nur Wahyuni Munir (International Journal of Nursing and Health Services (IJNHS), 2021)
International  Diabetes  Federation  (IDF) reported that the number of diabetes mellitus patients worldwide increases every year. Diabetes mellitus is a chronic disease due to damage to the pancreas in producing enough insulin and characterized by impaired metabolism of fats, increased blood sugar, carbohydrates and protein both absolutely and relatively. Diabetic foot ulcers (DFU) are among the most common complications in diabetic patients and are associated with high mortality, morbidity, and health costs.   This study was to determine the effect of health education on knowledge improvement about diabetic ulcers in the regional hospital of Tidore Islands.  This research is a quasi-experimental type with a pretest-posttest without a control group design. The research sample consisted of 30 respondents who met the inclusion criteria. Data were analyzed using a paired test and processed with statistic version 21. Based on the research results, there was an improved knowledge in pre and post-health education counseling, where the average score before health education counseling was 11.6. After health counseling, the average value was 15.0. The results showed the effect of knowledge in the prevention of diabetic ulcers with a p-value =0,000.  Health education is an effort to improve patient's ability to prevent diabetic foot ulcers that have been proven in several scientific studies. Health education methods provide additional information so that patients who previously wondered about their disease can directly ask health workers. Health education affects the knowledge improvement of Diabetes Mellitus patients in the Regional hospital of Tidore Islands